Effective Doses of Nalbuphine Combined With Propofol for Painless Gastroscopy in Adults: A Randomized Controlled Trial - Li, Shuangfeng; Wang, Ying; Chen, Xiaojian; Huang, Tingwan; Li, Na (Frontiers in Pharmacology, 2021)
Objective: This prospective study evaluated the 50% effective dose (ED50) and 95% effective dose (ED95) of nalbuphine combined with propofol during painless gastroscopy. Methods: Seventy-five patients who underwent painless gastroscopy were randomly divided into 5 groups (group N0, N0.05, N0.1, N0.15 and N0.2), with doses of 0, 0.05, 0.1, 0.15, or 0.2 mg/kg of nalbuphine in each group. Propofol was given to all groups as the sedative. The bispectral index (BIS) value, propofol dose, examination time, and awakening time were recorded. The number of patients with intolerance indexes (coughing, retching, swallowing, or limb movement) was recorded in each group. The ED50/ED95 of nalbuphine combined with propofol for gastroscopy were calculated. Results: Compared with group N0, N0.05, or N0.1, the propofol dose and awakening time were significantly reduced in group N0.15 or N0.2 (P < 0.05). The successful rate of painless gastroscopy in group N0.15 or N0.2 significantly increased compared to that of group N0 or N0.05 (P < 0.05). When combined with propofol, nalbuphine had an ED50 and ED95 for painless gastroscopy of 0.078 mg/kg (95% CI, 0.056 to 0.098 mg/kg) and 0.162 mg/kg (95% CI, 0.134 to 0.217 mg/kg), respectively. Conclusions: The ED50/ED95 of nalbuphine combined with propofol are 0.078 and 0.162 mg/kg, respectively, for painless gastroscopy. Nalbuphine at 0.162 mg/kg combined with propofol is effective and safe for painless gastroscopy in adults.